2012
DOI: 10.1007/s10661-012-2915-3
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of mycotoxins in feed samples in Burdur Province, Turkey

Abstract: The aim of this study was to evaluate the incidence of total aflatoxin (AF), ochratoxin A, T-2 toxin, deoxynivalenol (DON), zearalenone (ZEA), and fumonisin (FB) in dairy cattle, beef cattle, and lamb-calf feeds. A total of 180 dairy cattle, beef cattle, and lamb-calf feeds (60 samples each) were randomly collected from farms, feed mills, and villages in Burdur province, between September 2006 and August 2007. All samples were analyzed by the competitive Enzyme Linked Immuno Sorbent Assay (ELISA). The most fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…Occurrence of various endotoxins (aflatoxin, T-2 toxin, DON, ZEN, and fumonisin) except BUT and FUS C have been reported by using conventional methods like HPLC and ELISA in Turkey (17,18). Chemotyping studies of F. graminearum and F. culmorum isolates are focused on class B trichothecene detection (14,19).…”
Section: Discussionmentioning
confidence: 99%
“…Occurrence of various endotoxins (aflatoxin, T-2 toxin, DON, ZEN, and fumonisin) except BUT and FUS C have been reported by using conventional methods like HPLC and ELISA in Turkey (17,18). Chemotyping studies of F. graminearum and F. culmorum isolates are focused on class B trichothecene detection (14,19).…”
Section: Discussionmentioning
confidence: 99%
“…Doğan and Beyazıt (10) detected 62% AFB1 residue below 10 µg/kg and 8% AFB1 residue above 10 µg/kg in 100 feed samples collected from Kars province in Turkey. Şahindokuyucu Kocasarı et al (34) showed that the most common mycotoxin found in the feed stuff was aflatoxin (60%) in Burdur province, Turkey. Kaya et al (22) investigated mycotoxin residues in 1200 feed and feed stuff collected from different regions of Turkey by thin layer chromatography 1.08% of these samples were contaminated by mycotoxins.…”
Section: Discussionmentioning
confidence: 99%
“…The results of our study are in accordance with these studies (15)(16)(17). Many screening studies have been conducted to determine mycotoxin residues (4,(18)(19)(20). Oğuz et al (21) collected 150 feed samples from Konya and Mersin, and found that only 4 samples were contaminated with AFB1 (0.5-1 ppb).…”
Section: Discussionmentioning
confidence: 99%